Cardiac compartment-specific overexpression of a modified retinoic acid receptor produces dilated cardiomyopathy and congestive heart failure in transgenic mice. - Colbert, M C (1997)
Retinoids play a critical role in cardiac morphogenesis. To examine the effects of excessive retinoid signaling on myocardial development, transgenic mice that overexpress a constitutively active retinoic acid receptor (RAR) controlled by either the alpha- or beta-myosin heavy chain (MyHC) promoter were generated. Animals carrying the alpha-MyHC-RAR transgene expressed RARs in embryonic atria and in adult atria and ventricles, but developed no signs of either malformations or disease. In contrast, beta-MyHC-RAR animals, where expression was activated in fetal ventricles, developed a dilated cardiomyopathy that varied in severity with transgene copy number. Characteristic postmortem lesions included biventricular chamber dilation and left atrial thrombosis; the incidence and severity of these lesions increased with increasing copy number. Transcript analyses showed that molecular markers of hypertrophy, alpha-skeletal actin, atrial natriuretic factor and beta-MyHC, were upregulated. Cardiac performance of transgenic hearts was evaluated using the isolated perfused working heart model as well as in vivo, by transthoracic M-mode echocardiography. Both analyses showed moderate to severe impairment of left ventricular function and reduced cardiac contractility. Thus, expression of a constitutively active RAR in developing atria and/ or in postnatal ventricles is relatively benign, while ventricular expression during gestation can lead to significant cardiac dysfunction.